(untitled) (Journal of the Entomological Research Society, 2023)
New records for Türkiye of Ceutorhynchinae weevils are reported. Poophagus sisymbrii (Fabricius, 1977) is reported for the first time from Türkiye. In addition, Datonychus melanostictus (Marsham, 1802), Pelenomus commari (Panzer, 1795) and Rhinonchus bruchoides (Herbst, 1784), already known from the Anatolian part of Türkiye, are recorded for the first time from Turkish Thrace. Additional localities of a few species already known from Thrace region are also given.